Adsorptive Voltammetry of 4-chlordehydromethyltestosterone; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Moiseeva E. S. Evgeniya Sergeevna; Sheremetov A. M.; Nekhoroshev S. V.; Slepchenko G. B. Galina Borisovna (2014, 2014)
Title screen